Design and Build a Notary MIS Using the AES 256 Algorithm at a Web-Based Notary Office - Damanik, Arya Pratama; Suendri, Suendri (Journal of Information System and Informatics, 2024)
This research aims to design and develop a web-based Notary Management Information System (MIS) incorporating the AES 256 encryption algorithm to enhance data management and security in notary offices. Utilizing the Rapid Application Development (RAD) methodology, the system was developed through iterative collaboration between developers and users to meet both functional and non-functional requirements. Key features of the system include the management of order data, client records, notarial protocols, and user activity logs. The innovative application of the AES 256 algorithm ensures high-level data security, with validation tests confirming its effectiveness in protecting sensitive information. Performance testing demonstrated significant improvements, including a 40% reduction in data retrieval time and seamless encryption processes, compared to previous manual methods. The system also enhances accessibility and work efficiency through its web-based architecture. This research not only provides a practical solution for notary offices but also serves as a scalable model for secure MIS development in other industries.